Kerapatan dan Biomassa Pohon di Kampus Universitas Tanjungpura sebagai Kantong Karbon Kota Pontianak - Riza Linda,, Adityo Raynaldo, Rafdinal, (Jurnal Protobiont, 2018)
Tanjungpura University as an educational institution takes an important role in preserving the environment in Pontianak City, by prioritise green space and keep the trees around the campus remain sustainable. This research aims to know the total biomass and carbon stock at Tanjungpura University. The study was conducted from February to July 2017 at Tanjungpura University Pontianak, West Kalimantan. Carbon stock estimated by two categories, green space and administration and study area. Biomass estimated using allometric equation (Chave et al., 2005) by census every stand with DBH â‰¥ 5 cm. The results showed that total biomass ranged from 17,70-127,93 t/ ha with mean 71,10 t/ ha and carbon storage ranged from 8,85-63,97 t/ ha with mean 35,55 t C/ ha, and tree density mean 125,87 ind/ ha. Acacia mangium emerged as the highest carbon stock contributor in Untan (163,13 t C).